Revisiting the roles of individual phytochromes in red light-mediated arabidopsis growth and development by quadruple and triple mutant analyses - Hu, Wei; Lagarias, J. Clark (Frontiers in Photobiology, 2025)
Phytochromes are a small photoreceptor protein family regulating red/far-red light mediated plant growth and development. The five phytochromes in Arabidopsis, phyA-phyE, have distinct and overlapping functions partly due to their evolutionary divergence and heterodimerization. To define the regulatory roles of each phytochrome, quadruple mutants retaining only one phytochrome in the Landsberg erecta (Ler) accession of Arabidopsis thaliana were obtained and characterized. The most recently evolved phyB paralogs, phyD and phyE, individually poorly regulated red light-mediated seedling de-etiolation except for promoting cotyledon greening. The light-labile phyA positively regulated seedling photomorphogenic growth, dependent on its steady-state protein level in the light. PhyA specifically suppressed hypocotyl elongation under low red light but surprisingly antagonized phyB function under moderate red light to dampen photomorphogenesis. PhyB-only plants (a.k.a. phyACDE quadruple mutant) were significantly longer than Ler WT, which could not be complemented by any other phytochrome, thereby revealing that collective actions from more than two phytochromes are needed to achieve maximum photomorphogenic growth. In adult plants, phyB and phyE have undergone substantial subfunctionalization so that they equally and predominantly regulate photoperiodic flowering. Moreover, under short-day photoperiods, elevated light irradiance accelerated flowering of WT plants, delayed flowering of phyB-deficient plants, and had no statistically significant influence on flowering of phyB-only plants, unveiling the critical role of phyB to interpret the light intensity signal into flowering. The complete set of quadruple mutants and triple mutants retaining phyB and each other phytochrome represent foundational germplasms to assess genetic interactions between phytochromes and to explore phytochrome regulatory networks in response to varied environmental stimuli.